A computationally efficient P-LRU based optimal cache heap object replacement policy - Khan, Burhan Ul Islam; Olanrewaju, Rashidah Funke; Mir, Roohie Naaz; Khan, Abdul Raouf; Yusoff, Siti Hajar (Science & Information Sai Organization Ltd, 2017)
The recent advancement in the field of distributed computing depicts a need of developing highly associative and less expensive cache memories for the state-of-art processors i.e., Intel Core i6, i7, etc. Hence, various conventional studies introduced cache replacement policies which are one of the prominent key factors to determine the effectiveness of a cache memory. Most of the conventional cache replacement algorithms are found to be as not so efficient on memory management and complexity analysis. Therefore, a significant and thorough analysis is required to suggest a new optimal solution for optimizing the state-of-the-art cache replacement issues. The proposed study aims to conceptualize a theoretical model for optimal cache heap object replacement. The proposed model incorporates Tree based and MRU (Most Recently Used) pseudo-LRU (Least Recently Used) mechanism and configures it with JVM's garbage collector to replace the old referenced objects from the heap cache lines. The performance analysis of the proposed system illustrates that it outperforms the conventional state of art replacement policies with much lower cost and complexity. It also depicts that the percentage of hits on cache heap is relatively higher than the conventional technologies.